Voice science - Sataloff, Robert Thayer (Plural Publishing, Inc., 2017)
This book is designed to provide speech-language pathologists and other members of the voice team with a thorough grounding in the anatomical, physiological, and mechanical aspects of voice production, as well as an introduction to cutting-edge research in voice science. This book is a valuable asset for teachers and students in communication sciences, as well as otolaryngologists, speech-language pathologists, singing and voice teachers, and professional voice users.